Young Cattle Producers Conference Develops Leaders in Idaho - Carmen J. Willmore; Meranda Small; Sarah Baker; Jim Church ([TEST] Journal of Extension, 2021)
The need for young leadership in the beef industry has become a rising concern as the average age of primary operators increases. Extension educators developed a leadership conference for beef producers with the primary objective to educate and develop leadership qualities in young cattle producers. To achieve the objective participants, age 18-40 years old, had opportunities to learn all aspects of the industry through presentations, hands-on learning and industry tours. A post-conference survey revealed that participants planned to utilize what they learned and had a better understanding of the beef industry at the conclusion of the program.
Keywords: leadership training; cattle producers; young producers